2013
DOI: 10.1271/bbb.120391
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of the Production of Staphylococcal Enterotoxin A byStaphylococcus aureus

Abstract: We incubated 11 strains of Staphylococcus aureus in a brain heart infusion broth at 10-37 °C with two inoculum sizes and examined their enterotoxin A (SEA) production by a Western blot analysis to clarify the effect of incubation temperature on SEA production. Although SEA was detected in the exponential phase at 15-37 °C, it was also detected in the stationary or death phase at 10 °C. The maximal SEA concentrations of most strains increased as the temperature was increased, although some strains produced as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 35 publications
3
31
0
2
Order By: Relevance
“…The toxin concentration reached its maximum in the stationary phase of growth about 48 hours of incubation in the shaking culture. This was also observed for other SEA-producing strains Cao et al 2012;Tsutsuura et al 2013;Wallin-Carlquist et al 2010 . The time in the stationary culture was not clear because of its low production, but was estimated to be also about 48 hours of incubation Fig.2A .…”
Section: Sea Production Expression Of Sea Gene and Growth Of Strainsupporting
confidence: 62%
See 2 more Smart Citations
“…The toxin concentration reached its maximum in the stationary phase of growth about 48 hours of incubation in the shaking culture. This was also observed for other SEA-producing strains Cao et al 2012;Tsutsuura et al 2013;Wallin-Carlquist et al 2010 . The time in the stationary culture was not clear because of its low production, but was estimated to be also about 48 hours of incubation Fig.2A .…”
Section: Sea Production Expression Of Sea Gene and Growth Of Strainsupporting
confidence: 62%
“…Although the strains and culture conditions in the present study were different from those of Tsutsuura et al 2013 , the values shown in Table 3 were within their ranges.…”
Section: Figmentioning
confidence: 55%
See 1 more Smart Citation
“…aureus C‐29 [staphylococcal enterotoxin A (SEA) productive strain)] cultures maintained in our laboratory were used (Tsutsuura et al. ). These strains were subcultured on brain heart infusion (BHI) agar (Oxoid Ltd., London, UK).…”
Section: Methodsmentioning
confidence: 99%
“…In Europe, meat and related products have been the common food vehicles for SFP. In Japan, SFP frequently occurs in rice balls and Japanese-style desserts [24]. Food made by hand requiring no further cooking or handled frequently during preparation are major targets for Staphylococcus contamination and at highest risk for the production of bacterial toxins, which eventually cause SFP.…”
Section: Staphylococcimentioning
confidence: 99%